Benefit of crizotinib in a lung cancer patient with discordant ALK testing results. (2018) - Grocholski, Steven; Banerji, Shantanu; Qing, Gefei; Dawe, David E.
Abstract: Crizotinib is a first line treatment for patients with non-small cell lung cancer (NSCLC) harboring translocations in anaplastic lymphoma kinase (ALK). The current gold standard for determining ALK status is fluorescence in-situ hybridisation (FISH), but immunohistochemistry (IHC) is becoming increasingly popular due to lower cost. There are currently few reports on clinical outcomes with crizotinib therapy in patients who have tested negative by FISH and positive by IHC. A 53 year old lifelong non-smoking, physically active male with newly diagnosed Stage IV NSCLC presented with shortness of breath on exertion one month prior to referral. Staging CT scan failed to show a discreet lung lesion, but the left lower lobe was collapsed due to pleural effusion. Pleural fluid showed adenocarcinoma and IHC was positive for an ALK mutation, while FISH was negative. Pre-treatment PET-CT showed hypermetabolic, enlarged lymph nodes in the mediastinum and retroperitoneum. Partially due to patient concerns about cytotoxic chemotherapy toxicity, crizotinib therapy was instituted. Repeat CT conducted two months after crizotinib initiation showed a decrease in lymphadenopathy at all sites compared to the PET-CT. Furthermore, the patient showed clinical improvement, with less drainage through his PleurX catheter and stability of his excellent performance status. After 12 months on crizotinib CT showed ongoing improvement in lymphadenopathy. His bloodwork has been stable, and he denies significant drug toxicity. This case illustrates a sustained response to crizotinib therapy in a patient with an ALK translocation identified by IHC, but with negative FISH testing. The literature suggests that the population with these discordant results could be up to 19% of ALK positive NSCLC. Patients in this subgroup who are receiving crizotinib should be identified and outcome data pooled. However, in the interim, oncologists may wish to consider targeted therapy for these discordant patients.